Short-run effects of economic reforms in Eastern Economies - Franz Peter Lang (Intereconomics, 1991)
The policy of reform in the former Eastern Bloc countries is relying on introducing the mechanisms of the market economy. However, the process of putting such changes into practice with concrete measures has to overcome a number of impediments which have so far hardly been considered by the reformers. The impediments are partly generated by rigidities which are an inevitable aspect of the adjustment process from a planned to a market economy.
Keywords: 330; Eastern Europe